LAKI-LAKI VERSUS PEREMPUAN DI ERA KOMPETISI (Analisis Kesetaraan Dalam Islam) - Rasyid, Muh. Haras (DIKTUM: Jurnal Syariah dan Hukum, 2010)
Men and women were created with the same purpose to serve Allah swt. in various aspect of life. This paper raised the issue that started from a reality in a different society with the purpose of human creation. With the purpose, will be understood correctly that the presence of men and women are aqual, because it comes from and the purpose of creating the same. Then it is not only to understandable, but practiced in life everyday. Recognized the existence of the difference, but not a reason the inequity between of both. This paper focuses with the approach of theology an sociology, by analyzing the Quran and hadis, and social realites.